Prescribing patterns in patients using new antidepressants - Meijer, Welmoed E E (Blackwell Science Inc, 2001)
AIMS: To study possible selective prescribing (‘channelling’) we compared characteristics of patients using the SSRI sertraline with patients using longer available SSRIs. METHODS: An observational cohort study in 1251 patients being prescribed an SSRI. RESULTS: In contrast to other studies, we found no evidence for channeling of sertraline. Sertraline was mainly prescribed for the labelled indication (depressive disorder), while older SSRIs were more often prescribed also for other indications. Time on the market was inversely associated to the proportion of patients treated for depressive disorder. CONCLUSIONS: We found no evidence for channeling of sertraline compared with prescribing patterns of older SSRIs.